The Effectiveness of Team Assisted Individualization in Teaching Vocabulary Viewed from Studentsâ Motivation - *, Sulaiman (Sebelas Maret University, 2016)
This research reveals an experimental study about the effectiveness Team Assisted Individualization inteaching vocabulary at private university in Pontianak. The population of this research was the first semesterÂ students of university in Pontianak. The sample was two classes consisting of 60 students taken by usingÂ cluster random The data analysis was done by applying descriptive and inferential statistic (ANOVA andÂ Tukey Test) to test the research hypothesis. Based on the results of the analysis, the findings of this researchÂ are: (1) the students who are taught by using Team Assisted Individualization have better vocabulary masteryÂ that those who are taught Peer tutoring. In other word, the use of Team Assisted Individualization is moreÂ effective than Peer Tutoring in teaching Vocabulary; (2) the students having high motivation have betterÂ vocabulary mastery than those having low motivation; and (3) there is interaction between teaching methodÂ and motivation toward studentsâ vocabulary mastery. Based on research findings, it can be concluded thatÂ Team Assisted Individualization is an effective teaching method to teach vocabulary for the first semesterÂ students of university in Pontianak. The effectiveness of the method is influenced by the studentsâ level ofÂ motivation.